Monsters and men [videorecording (DVD)] - Green, Reinaldo Marcus, 1981-; Washington, John David, 1984-; Ramos, Anthony; Harrison, Kelvin, Jr., 1994- (Universal Pictures Home Entertainment, 2019)
The aftermath of a black man being killing by a police officer. The story is told through the eyes of the bystander who filmed the act. A high school baseball phenomenon and an African-American police officer were inspired to take a stand.